Nic Bishop butterflies and moths - Bishop, Nic, 1955- (New York : Scholastic Nonfiction, 2009)
Full-color photographs and illustrations describe the physical characteristics, behaviors, habits, and life cycle of butterflies and moths.
Includes index.
Book Links (A.L.A.)
School Library Journal starred
Wilson's Children
Book Links (A.L.A.), January 2010
Booklist starred, June 2009
Keywords: Butterflies -- Juvenile literature; Moths -- Juvenile literature; Butterflies; Moths; Butterflies; Moths